Prophecy and Dissent, 1914-16 - Russell, Bertrand 1872-1970; Rempel, Richard A.; Frohmann, Bernd; Lippincott, Mark; Moran, Margaret (London Unwin Hyman, 1988)
Bertrand Russell's shorter writings against British participation in the First World War from its outbreak until the formation of Lloyd George's coalition. It includes the fullest documentation yet of the continuing government attempts to stifle Russell, then regarded as Britain's most dangerous pacifist.
Keywords: 20th Century (1901-2000); World War I (1914-1918); Philosophy; United Kingdom